Non-resident students’ rental preferences in Seri Iskandar, Perak - Mazlizan, Irfan Wafiq (2024)
This research investigates the rental preferences of non-resident students in Seri Iskandar, Perak, focusing on key factors that influence their housing decisions. With the increasing number of students attending universities in Seri Iskandar and the corresponding rise in demand for rental accommodations, understanding these preferences is crucial for various stakeholders, including students, landlords, and university administrators. The study employs a quantitative data from structured questionnaires. The sample includes non-resident students from various higher education institutions in Seri Iskandar, providing a diverse and representative understanding of the population. Key findings indicate that location is the most significant factor influencing rental decisions, with students prioritizing proximity to their institutions. This is followed by rental cost, which is a critical concern given the financial constraints many students face. Housing quality, type of accommodation, and rental tenure also play substantial roles in shaping preferences. The demographic analysis reveals that factors such as age, gender, marital status, and financial resources significantly impact rental choices. Furthermore, the study highlights that students' academic level and year of study influence their housing requirements and preferences. Overall, this research provides a comprehensive understanding of non-resident students' rental preferences in Seri Iskandar, offering practical implications for improving student housing and contributing to the broader discourse on student accommodation in higher education contexts.